PENINGKATAN PRODUKTIVITAS PADI LAHAN RAWA LEBAK MELALUI PENGGUNAAN VARIETAS UNGGUL PADI RAWA (Jurnal Pertanian Tropik, 2015)
In 2014 the total area of rice fields in North Sumatra was 464 827 ha, which has a land area of irrigated rice 291 062 ha, while the non-irrigated rice land area of 173 765 ha. Non irrigated wetland is classified into three agro-climatic types include 1). Rainfed areas, 2). Tidal wetland and 3). Lowland swamp wetland or non-tidal swamp. The potential development of swamp wetlands for paddy is still open because of the productivity is still low. Causes of low productivity such as soil fertility are relatively low, it still uses the old local varieties in 5-6 months, varieties that have been hereditary, and land management is still relatively conventional. Through the Integrated Crop Resource Management approach (PTT), swamp wetlands have the potential to be developed and are expected to become a contributor to rice production significantly. The aim of this research is to provide the technology package for lowland swamp rice cultivation in North Labuhan Batu Regency, North Sumatra Province. The research was conducted in the village of Sidua-Two, Sub District of South Kualuh, North Labuhan Batu district, from April to September 2014. Research using randomized block design (RBD) with 7 treatment swamp rice varieties that Inpara1, Inpara2, Inpara3, Inpara4, Inpara5, Margasari and varieties that farmers commonly planted the Mekong. Treatments were replicated three times, cooperator farmers used as replication with a plot area of 20m x 25m with a total area of 1ha. The results showed that the varieties Inpara1, Inpara2, and Inpara 3 provide the highest productivity compared to other varieties. Additionally varieties Mekongga still gave good productivity in lowland swamp. The main obstacle a lowland swamp land development is waterlogging, and unpredictable drought, depending on the circumstances of hydro topography, rainfall, and water level of local rivers. Results of soil analysis showed the content of micro-nutrients such as Al, Fe, Mn, Band Sare also included a higher category. The high content of elements Al and Fe cause soil reactions that are highly acidic soil and the soil pH is very low. Recommendations on a package of rice cultivation in shallow lowland swamp land need to be implemented in order to increase the productivity of lowland swampland.